A Juridical Analysis of the Implications of Constitutional Court Decision No. 60/PUU/XXII/2024 Paving the Way for Political Parties Without Regional Representative Council Seats in Nominating Regional Heads - Waisapi, Jeffry Yuliyanto (Journal of Law, Politic and Humanities, 2024)
The Constitutional Court's Decision No. 60/PUU/XXII/2024 has altered the nomination requirements for regional head elections, allowing political parties without seats in the Regional Representative Council to nominate candidates. This change is seen as a progressive step in strengthening democracy by broadening opportunities for small and emerging parties. However, it also introduces risks and challenges, such as the potential reinforcement of political dynasties, increased money politics, and political fragmentation at the local level. This study aims to analyze the juridical implications of the decision on Indonesia's regional head election system. The research method employed is normative legal method with a juridical analysis approach to relevant legislation, including the 1945 Constitution, the Regional Head Election Law, and Decision No. 60/PUU/XXII/2024. The study's data sources are secondary, comprising legal documents, academic literature, and news articles discussing related issues. The findings indicate that while the decision has the potential to expand political participation and strengthen democracy, significant risks related to political stability and the integrity of the election process remain. Therefore, strict oversight and effective law enforcement are necessary to ensure that these changes positively impact Indonesia's democracy.